The Effect of Foreign Ownership and Managerial Ability on Earning Quality with Committee Audit as Moderating Variable - Sylvia Dwi Lestari; Azwardi Azwardi; Tertiarto Wahyudi (Облік і фінанси, 2020)
This study aims to investigate the effect of foreign ownership and managerial ability on earning quality with committee audit as moderating variable. The authors used secondary data that was obtained from annual report. The sample used in this study contains 28 manufacturing companies listed on Indonesian Stock Exchange from 2014 to 2018. The sample was selected using purposive sampling. Earning quality as dependent variable is measured by discretionary accrual Jones Model. Foreign ownership is measured by the number of foreign ownership compared with the number of ownership structure. Managerial ability is measured by efficiency using data envelopment analysis (DEA). Efficiency is used for knowing the managerial ability on manage output and input of the companies. Committee audit as moderating variable is measured by the number of committee audit who has accounting / auditing / finance background / experience compared with the number of committee audit of companies. Data analysis method use panel data regression analysis for testing hypothesis. To find out how the effect of foreign ownership and managerial ability on earning quality is moderated by committee audit using moderated regression analysis (MRA). The result of this study showed that foreign ownership and managerial ability simultaneously have significant effect on earning quality. Partially, foreign ownership has no significant effect on earning quality. While, managerial ability has positive and significant effect on earning quality. Meanwhile, committee audit can moderated the effect of foreign ownership on earning quality, and the effect of managerial ability on earning quality.